PERENCANAAN SISTEM PERSEDIAAN BAHAN BAKU PRODUK X SOLAR WATER HEATER DI PT. XYZ - Tandi, Matius Marthen; Sulistyadi, Kohar; Ratnasari, Lisa (Prodi Teknik Informatika Universitas Sahid Surakarta, 2020)
PT. XYZ is a company engaged in the water heater industry (solar water heater) located in Bogor, West Java. Currently the company does not have a raw material inventory method, because the company does not have a fixed schedule for ordering raw materials, so there is often a vacuum of raw materials. WinQSB version2.0 is a quantitative management analysis software used to process data. Based on the results of data processing obtained a group of components that have the largest inventory costs, namely group A (Electric Heater, Thermostate, and ELCB). The value of economic order quantity (EOQ) 3208Pcs with a total cost of IDR 2,553,370,500, the amount of safety stock is 80Pcs, and the value of ROP (Reorder Point) is 497Pcs, which means the company must have 80 safety stock of raw materials each component and when the raw material stock reaches 497 must be re-ordered. The total cost with the Period Order Quantity (POQ) order quantity (Q) analysis is Rp2,611,285,900, and the total cost with the period order analysis is Rp2,541,200,900. So it is recommended to the company to implement an inventory system with an analysis of Period Order Quntity (POQ) based on the order period (P) because it can save inventory costs by Rp.182,563,934.